Photoelectron-Photofragment Coincidence Spectroscopy With Ions Prepared in a Cryogenic Octopole Accumulation Trap: Collisional Excitation and Buffer Gas Cooling - Shen, Ben B.; Lunny, Katharine G.; Benitez, Yanice; Continetti, Robert E. (Frontiers in Chemistry, 2019)
A cryogenic octopole accumulation trap (COAT) has been coupled to a photoelectron-photofragment coincidence (PPC) spectrometer allowing for improved control over anion vibrational excitation. The anions are heated and cooled via collisions with buffer gas <17 K. Shorter trapping times (500 μs) prevent thermalization and result in anions with high internal excitation while longer trapping times (80 ms) at cryogenic temperatures thermalize the ions to the temperature of the buffer gas. The capabilities of the COAT are demonstrated using PPC spectroscopy of O3- at 388 nm (Ehν = 3.20 eV). Cooling the precursor anions with COAT resulted in the elimination of the autodetachment of vibrationally excited O2- produced by the photodissociation O3- + hν → O + O2-(v ≥ 4). Under heating conditions, a lower limit temperature for the anions was determined to be 1,500 K through Franck-Condon simulations of the photodetachment spectrum of O3-, considering a significant fraction of the ions undergo photodissociation in competition with photodetachment. The ability to cool or heat ions by varying ion injection and trapping duration in COAT provides a new flexibility for studying the spectroscopy of cold ions as well as thermally activated processes.